BCT599: Bio-Composite Technology II / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2016)
The course will review the general technology of composites, and focus on the bio-based composites field for particle-based, fiber-based and flour composite (Chipboard, MDF. and paper). It also provides an overview of bio-based composites products as an increasingly important part of the wood utilization industry. The advantages of composite technology as a viable solution to material limitations in both natural and manufactured products, and draw from this the reasons for the development of bio-based composites as a solution that maximizes the use of the forest resource. A generalized composite model is described in terms of particle size, and orientation, and adhesive systems. The product and process requirements will be considered in terms of chemical characteristics and structure; material requirements; preparation; resin technology; presses (particularly continuous press technology); panel performance requirements and test procedures; and environmental impacts of both products and processes. The performance of composite panels is considered in relation to market requirements, and from an environmental perspective. Field trips will be undertaken to familiarise students with the manufacture and recent technology of wood and bio-based composites products in Malaysia.